Conformismo e espontaneísmo em Gramsci: da prática pedagógica à práxis político-pedagógica - Nascimento, Lorivaldo do (2023)
The research approaches the political-pedagogical category of the new Gramscian conformism in its critical dialogue with the different forms of spontaneity present in folklore, common sense, religious beliefs linked to the Catholic Church, the educational reforms that occurred in Russia and Italy, and, finally, the economical and mechanistic positions of Marxist thinkers such as Sorel, Rosa Luxemburg, Trotsky, Bukharin, and the Communist International itself. The aim is to understand, based on Gramscian writings, his political-pedagogical conceptions related to the historical conjuncture and the theoretical debate of the last decades of the 19th century and the first decades of the 20th century. The discussion presupposes a set of dialectical relations between the different perspectives, the historical context and the theoretical support of the thinkers with whom Gramsci dialogues. For this purpose, based on the assumption that history needs to be understood as a science concerning the human process of the production of its material, social, and cultural existence, the aim was to understand the Gramscian texts in the complexity, contradictions, and uncertainties of their context, as well as to capture the different understandings of the interrelations of school education with society. Finally, it seeks to establish the debate with the different interpretations of Gramscian thought considered in a historical-material praxis, which reveal different theoretical conceptions about the revolutionary process in the concrete dialectical relationship between the economic structure and the superstructures of politics and pedagogy. As primary sources the Gramscian texts in the original Italian edition of Gerratana were used, especially the Prison Notebooks. As secondary sources are used theses, books and specialized articles by Italian and Brazilian theorists who have conducted analyses on Gramsci and his context. The conformism advocated by Gramsci is synonymous with a proposal for education that aims to promote catharsis, intellectual and moral reform. The proposal relates to the totality of the political-pedagogical categories of his thought, in particular class struggle and the unique school. In this way, through the action of intellectuals, the subordinate classes are conformed according to their own conception of the world and overcome bourgeois conformism, to which the different forms of spontaneism corroborate.